Enhancing Project Efficiency and Business Overall Performance Through Measuring the Impact of SCM System, Employee Skills, And Project Agility - Abu-Rumman, Mohammed A.; Hatamleh, Amer Ahmad; Alhyasat, Khaled M.K.; Qutieshat, Rania J.; Hanandeh, Ahmad (Journal of Posthumanism, 2025)
This research aims to study the effects of SCM implementation, Employee skills, an/3q d environment agility on project Efficiency and business overall performance. The goal of defining these variables interact is important and critical for competitiveness in unstable environment with a rapid innovative change in technological field. The research chose Zain organization in Jordan in order to conduct this research, a questionnaire of 25 questions has been designed to collect all the needed information about SCM system, employee skills, and environment agility to enhance the project Efficiency and business overall performance. The relationship between the research's variables has been measured based on 171 responses valid for statistical analysis using SEM. The main result of this research summarized that employees should have high technical skills in using SCM system which could be significantly affects enhancing project Efficiency and conduct professionally the business overall performance. Furthermore, this research concluded that apply SCM system is critical to deal with huge amount of data and information, rapid technological change, and rapid changes in job market and turbulent competition.